A review of biological drinking water treatment technologies for contaminants removal from polluted water resources. (February 2020) - Abu Hasan, Hassimi; Muhammad, Mohd Hafizuddin; Ismail, Nur 'Izzati
Graphical abstract: Highlights: Biological process via biofilms is a new concept for the water treatment. It is considered a 'future technology' for the water treatment. The treatment processes have the capability to treat various types of contaminants. There have been limited studies and application performed in developing countries. The technology is still unacceptable by the most water treatment practiser and consumer. Abstract: This paper is the first critical review of the technology of water treatment via biological process for contaminants removal from water resources. The biological process is considered the future for drinking water treatment, especially for developing countries. The main focus of the review is on single and integrated treatment technologies that have been studied for all types of drinking water resources, including surface water and ground water. These treatment technologies have the capability to treat contaminants in polluted drinking water resources, such as heavy metals, natural organic matter, inorganic non-metallic matter, disinfection by-products, endocrine disrupting chemicals and microbial contaminants. The potential threats and challenges of using the biological process for safe drinking water production also have been discussed, as this technology is a relatively new concept for safe drinking water production, and there have been very limited studies performed in developing countries.